Analysis of the application of buteyko breathing exercise to improvement of respiratory rate (RR) and oxygen saturation (SpO2) in asthma patients in the emergency room RSUP Dr. Kariadi - Mursjid Djiwandono, Saadillah; Trisnaningtyas, Wenny; Utami Dwiningsih, Sri; Dafid Zakaria, Eka; Nisa, Rif’atun (Jurnal Keperawatan, 2023)
Introduction: Asthma is a chronic inflammatory disease of the respiratory tract characterized by coughing, shortness of breath, wheezing, and a feeling of heaviness in the chest, which is generally reversible both with and without treatment. Giving Buteyko breathing exercise action is more effective than before being given the action. Objectives: To analyze the application of Buteyko breathing exercises to improve respiratory rate (RR) and oxygen saturation (SpO2). Methods: Descriptive analysis in the form of case studies with total sampling based on inclusion and exclusion criteria of 3 patients under management. The Buteyko breathing exercise was applied, and vital signs were observed before and after the Buteyko breathing exercise. Results: Nursing problems are ineffective breathing patterns with Respiratory Rate (RR) > 26 x/minute, and two patients were found to have mild hypoxia with SpO2 <95%. After applying the Buteyko breathing exercise, the three patients experienced an improvement in their condition with RR 18-20 x/minute and SpO2 > 98%. The author describes the application of Buteyko breathing exercises to asthma patients, which improved the condition of RR and SpO2. They were supported by Lisavina's research (2019) on the difference between controlling asthma before and after implementing Buteyko breathing. Conclusions: The application of Buteyko breathing exercises in assessing improvement in respiratory rate (RR) and oxygen saturation (SpO2) did not harm patient conditions, hospital costs, time and effort, or infrastructure.